STRATEGI PERLINDUNGAN BRANDING BATIK KOTA PEKALONGAN MENYONGSONG AFTA 2015 : IDENTIFIKASI, DAN SOLUSI PENERAPAN SOP (STANDARD OPERATING PROCEDURE) â€œHEALTH ENVIRONMENT & SAFETY WORKERâ€ - Latif, Rr. Vita Nur; Ristiawati, Ristiawati; Istiqomah, Nor (JURNAL LITBANG KOTA PEKALONGAN, 2014)
Background : AFTA (ASEAN Free Trade Area) is a form of free trade which requires Indonesia to be excellentin terms of products that promote not only quality products but also processes, ensuring quality and standards. Indonesian batik has been recognized by UNESCO as an in tangible cultural Indonesian nation, which mustbeone of exellent products that will participate in the AFTA. Branding the world city of batik for Pekalongan, a positive consequence very proud. But on the other side of the batik processis generally still dependent on raw materials hazardous material negative impact on workers and the environment. The purpose of this study rests on the demands of AFTA (ASEAN Free Trade Area) in 2015 is to improve the quality and the quality and the protectionof domestic products (batik) to be able to compete with foreign products brought marketable products, wherethe production process considering various aspects of health and safety works. Technical outputis generated in the form of data on workers health problems batik, and identification of wastes in this production of Pekalongan City in 2014 through the study and measurement of epidemiology and Environmental Health. Such data as one of the keyst in batik branding strategy formulation protection in the form of a draft SOP and healthy environment for the workers to wards the implementation SMK3 the batik industry with zero accident and zero cases. Results. Batik worker health problems in the form of 67.5% lungcapacity disorders; 33.8% decrease invisual function; dermatitis extremities 30%. Distribution of workers with impaired lung capacity, decreased visual function, and dermatitis extremities were observed at the stage of wax sticking, respectively 64.8%; 48.1%; and 66.7%. While the profile of batik waste outlet or point before entry into free waters showed temperature (30 o C), pH(9), and COD (18.7 ppm) waste is under the maximum level (safe), where as the levels of BOD(162 ,2ppm) as of yet safe because it is still above the maximum levels of environmental quality standards. Conclusion :Some of the health problems in batik workers found that lung capacity disorders, visual impairment, and dermatitis extremities. While batik waste profile shows temperature, pH, TSS, and COD are under environmental quality standards, but still above the levels of BOD quality standards. Keyword: Batik, health problems, waste